Beaches as a factor in achieving competitiveness of a tourist product : case study: Istrian County - Zadel, Zrinka (Array, 2018)
Beaches are the main part of an integral tourist product of a destination. They represent a highly valuable resource from the aspect of natural, social, economic and recreational potential. They make a tourist product attractive, and represent a motive of arrival to a destination for a certain number of tourists. In order for a beach to be placed in a function of tourist offer and positioning of a tourist destination on the tourist market, and for destination´s tourist product to become more attractive, it is necessary to enrich the offer of beaches according to the desires of market segment while respecting the principles of sustainable development. Beach offer of the Istrian County has been analysed within this paper. While preparing this paper, the authors have used the scientific methodology, which means gathering and the analysis of data from primary and secondary sources. An analysis of domestic and foreign professional and scientific literature has been carried out, as well as the valid law frame of beach managing in the Republic of Croatia. With a goal of analysing the existing state of regulation and managing beaches in the Istrian County, an evaluation of beach resources has been carried out.